Production of mycophenolic acid by Penicillium roqueforti strains. - Lafont, P (1979)
Sixteen strains of Penicillium roqueforti Thom, isolated from blue-molded cheeses, were studied. In vitro, all of these strains produced mycophenolic acid, some on the order of 0.8 to 4 mg/g od dry culture. The greatest yields were obtained after 10 days of incubation of cultures at 15 degrees C. However, under some experimental conditions, mycophenolic acid was not alone responsible for the toxicity of culture extracts to chicken embryos.